2011
DOI: 10.1111/j.1365-2656.2011.01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the demographic buffering hypothesis with vital rates estimated for Weddell seals from 30 years of mark–recapture data

Abstract: Summary1. Life-history theory predicts that those vital rates that make larger contributions to population growth rate ought to be more strongly buffered against environmental variability than are those that are less important. Despite the importance of the theory for predicting demographic responses to changes in the environment, it is not yet known how pervasive demographic buffering is in animal populations because the validity of most existing studies has been called into question because of methodological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 90 publications
7
105
0
Order By: Relevance
“…The apparent behavioural response of seals was in keeping with a strategy of saving and allocating a larger proportion of energy to survival, as would be expected in a long-lived organism [9,33]. The ability to buffer adult survival against environmental variability by adjusting reproductive effort has already been shown in this population [44], but previous work did not investigate the particulars of the iceberg event. Here, by explicitly assessing how demography during the iceberg period contrasted with that recorded in years with typical conditions, we demonstrated that the iceberg event had a substantial impact on reproduction, but that survival was well buffered from environmental variation.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The apparent behavioural response of seals was in keeping with a strategy of saving and allocating a larger proportion of energy to survival, as would be expected in a long-lived organism [9,33]. The ability to buffer adult survival against environmental variability by adjusting reproductive effort has already been shown in this population [44], but previous work did not investigate the particulars of the iceberg event. Here, by explicitly assessing how demography during the iceberg period contrasted with that recorded in years with typical conditions, we demonstrated that the iceberg event had a substantial impact on reproduction, but that survival was well buffered from environmental variation.…”
Section: Discussionmentioning
confidence: 88%
“…Because vital rates are probabilities, their maximum possible variance is a function of the mean [10]. Therefore, following previous authors [9,10,15,44], we scaled the process variance by the maximum possible variance for the corresponding mean before making comparisons among different periods. For local abundance estimates, which were obtained independently for each year, the method of moments was performed in program R (v. 2.12.0, [46]), using the generalized weighted procedure [41].…”
Section: Iceberg Impact On Weddell Seals T Chambert Et Al 4533 (I) mentioning
confidence: 99%
See 2 more Smart Citations
“…If we assume that most density-dependent changes in vital rates are driven by consumption, then what are often thought of as density-dependent responses in vital rates are more usefully analyzed as consumptiondependent responses in vital rates that control the abundance of predators. We expected these responses to adhere to density-dependent patterns in that juvenile survival and reproductive rates should be the most responsive to changes in the per capita prey consumption rates of killer whales, as in other large mammals (Eberhardt & Siniff 1977, Gaillard et al 1998, Eberhardt 2002, Rotella et al 2012). This expectation was confirmed by a high degree of consumption-dependence (p << 0.05; Fig.…”
Section: Consumption-dependence and Predator-prey Dynamicsmentioning
confidence: 99%